Three formats of multi-methodological teaching applied to urban planning - Martínez-Baldares, Tomás (2023)
Practice and active learning are key processes in the last cycle of training of the architect. This article documents a methodological scheme to make effective the link with government institutions that allow spaces for the practical application of training most important topics. This article presents the methodology developed in three different modalities with three applied cases: professional practice, final graduation project and teaching. Each of the three formats allude to a specific case that was successfully developed in an institutional setting. The process identified three key difficulties: the relevance and alignment with the political proposal, the identification of the interlocutor or link, and the ease of accessing the territory and information about it. From these, a proposal was designed to solve these barriers and build a fluid process with a constant interaction mechanism. The result can have a positive impact on the way of achieving a dual, effective training that is closest to professional practice.